Blood Pressure Screening at a Non-Government Tertiary Care Hospital in Bangladesh: A Pilot Study - Khanom, Mehrunnissa; Chowdhury, Md Akhtarul Islam; Hossain, Md Amir (Bangladesh Heart Journal, 2022)
Objective: The general Objective of this pilot study was to unveil the findings of blood pressure screening program at a Non-Government Tertiary Care Hospital in Bangladesh. The specific Objectives were to find out socio-demographic profile of the participants, to categorize the blood pressure readings according to the defined variables, to select among the participants who would require intervention and to encourage people in order to adopt healthy diet as well as lifestyle behaviors. Methods: It was a cross-sectional study conducted at outpatient department of Chattagarm International Medical College Hospital (CIMCH), Shamsherpara, Chattogram from 16.05.2022 to 19.05.2022. The study participants were volunteers of 18 years or older who wished to get the free blood pressure checkup on observation of world hypertension day at CIMCH outpatient premises. Results: Altogether 232 patients participated in the blood pressure screening program, 10.7% were pre-hypertensives and 11.2% had high blood pressure; none of them visited any physician previously for checking blood pressure. Pre-existing hypertensives constituted 16.4% of total participants; nearly half of them had good compliance to medication or life style modification. The maximum (26 out of 51) ‘pre-hypertensive’ and ‘high blood pressure’ were in the 30-49 years age group. Conclusion: Community based blood pressure screening and patient education covering a wider area can be an effective approach to reduce the burden of hypertension as well its conquences on the patient, family, society, nation, and the globe. The Results of the current pilot study might provide preliminary data and encourage for future prospective studies. Bangladesh Heart Journal 2022; 37(2): 84-88